Phosphorylation of GIT1 tyrosine-392 is required for PLCγ activation and podosome formation in vascular smooth muscle cells - Wang, Jing (2010)
OBJECTIVE: Podosomes, actin-rich structures, contribute to cell motility, matrix remodeling and tissue remodeling. We have shown that G-protein coupled receptor kinase 2-interacting protein 1 (GIT1) co-localizes with podosomes, and is important in podosome formation in endothelial cells. Src stimulates GIT1 tyrosine phosphorylation, which is critical for phospholipase C-γ (PLCγ) activation. Here we identified specific GIT1 tyrosines required for PLCγ activation and podosome formation in vascular smooth muscle cells (VSMC). METHODS AND RESULTS: We used phorbol 12, 13-dibutyrate (PDBU) to induce podosomes in A7r5 VSMC. GIT1 co-localized with podosomes and GIT1 knockdown using siRNA significantly reduced podosome formation. PDBU stimulated GIT1 tyrosine phosphorylation. GIT1 tyrosine-phosphorylation was dramatically decreased in SYF−/− cells, and also was reduced by pretreatment with the PKC and Src inhibitors, suggesting that GIT1 phosphorylation was dependent on PKC and Src. By mutation analysis of multiple tyrosines, we found that PDBU specifically increased GIT1-Y392 phosphorylation. Overexpression of GIT1 (Y392F), but not GIT1 (Y321F), decreased PDBU-mediated PLCγ activation and podosome formation without effect on ERK1/2 activation. Additionally, we provide evidence that GIT1 KO VSMC have markedly fewer podosomes upon PDBU treatment compared to WT VSMC. These data show that GIT1 is a key regulator of podosome formation in VSMC. CONCLUSIONS: In conclusion, our data suggest that GIT1-Y392 phosphorylation is critical for PDBU-induced podosome formation by regulating PLCγ activation. We propose that specific signaling modules are assembled in a GIT1 phosphotyrosine-dependent manner as exemplified by PLCγ activation versus ERK1/2 activation.